Virus-Induced Anterior Uveitis (VIAU) in Immunocompromised Patients (2018)
Purpose: To describe the clinical characteristics, diagnosis, and treatment of VIAU in immunocompromised patients. Methods: A critical review of literature was performed. Results: Diagnosis and treatment of VIAU in immunocompromised patients may be a challenge due to atypical clinical-courses, severe presentations, and more frequent recurrences. A conclusive diagnosis can be made by aqueous-humour PCR-analysis. Visual prognosis depends on early diagnosis and prompt treatment. Frequent ocular examinations are recommended in HIV patients with CD-4-counts below 100 in order to rule out opportunistic ocular coinfections. It is essential to bear in mind the potential side-effects of therapeutic interventions and consider the possibility of Immune Recovery Uveitis (IRU) in eyes with treated viral retinitis after the initiation of HAART. Conclusions: Early diagnosis and treatment of VIAU in immunocompromised patients can be achieved with high suspicion, recognizing clinical features, and obtaining specimens for molecular diagnostic testing in order to avoid usually severe ocular morbidity. ©, © Taylor and Francis Group, LLC.